Cancer cell-derived tissue factor-positive extracellular vesicles: biomarkers of thrombosis and survival. Issue 5 (September 2019) - Hisada, Yohei; Mackman, Nigel
Abstract : Purpose of review: Tissue factor (TF) is released from cancer cells and tumors in the form of extracellular vesicles (EVs). This review summarizes our current knowledge of the mechanisms of release of TF-positive EVs (TF+EVs) from cancer cells and the effect of these TF+EVs on cultured endothelial cells. In addition, we will summarize the contribution of TF+EVs to thrombosis in mice, and the association between plasma EVTF activity and venous thrombosis as well as survival of cancer patients. Recent findings: The release of TF+EVs from cancer cells is regulated by multiple factors, including hypoxia, epithelial–mesenchymal transition, and various intracellular signaling pathways. Cancer cell-derived, TF+EVs confer procoagulant activity to endothelial cells and induce the expression of adhesion proteins and IL-8. In addition, they contribute to thrombosis by directly activating the coagulation system and by generating thrombin that activates platelets in mouse models. Finally, there is an association between EVTF activity and venous thrombosis in pancreatic cancer patients as well as mortality in cancer patients. Summary: Cancer cell-derived TF+EVs bind to and activate endothelial cells. In addition, they serve as biomarkers of survival of cancer patients and venous thrombosis in pancreatic cancer patients.